Degradación del cristal violeta presente en aguas residuales mediante la oxidación catalítica húmeda con peróxido de hidrógeno (CWPO) a partir de óxidos mixtos de MN-CU a condiciones moderadas (2018)
Industrialization has generated the development of new production technologies in conjunction with control policies regarding the dumping of waste and by-products emanating from each of the stages, taking into account the protection of the environment; This is how the removal of highly toxic substances such as synthetic dyes generated in the effluents of different industries from novel, efficient and profitable techniques on an industrial scale is sought. The catalysts of mixed oxides Mn and / or Cu in different molar ratios were prepared from the auto combustion method and characterized by the techniques DRX, TPR-H2, isotherms of adsorption-desorption of N2 and atomic absorbance. The solids are evaluated in the degradation of the violet crystal (CV) by the catalytic oxidation in humid phase with H2O2 under moderate conditions of reaction: temperature at 25 ° C, ambient pressure, air flow of 2 mL / min and 0.1M 2ml / h of H2O2, showing high activity and selectivity. The experimental results showed degradations of 100% of the CV, conversion of the total organic carbon (TOC) of 74%, elimination of the COD of 71%, in approximate times of 90 minutes of reaction. Additionally, the selectivity is monitored by CG-MS, finding that there is almost complete mineralization in a short reaction time, generating intermediate products of carboxylic acids, alcohols and amines that do not cause a serious risk to the environment. The MnCu catalyst with molar ratios of 1: 2 proved to be the most promising catalyst showing a cooperative effect between the two metals and the importance of the redox properties for the elimination of the CV dye in wastewater.